Thermodynamic modeling of the Na-X (X = Si, Ag, Cu, Cr) systems - Hao D.; Bu M.; Wang Y.; Tang Y.; Gao Q.; Wang M.; Hu B.; Du Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The Na-X (X = Si, Ag, Cu, Cr) systems have been critically reviewed and modeled by means of the CALPHAD approach. The two compounds, NaSi and Ag2Na, are treated as stoichiometric ones. By means of first-principles calculations, the enthalpies of formation at 0 K for the LT-NaSi (low temperature form of NaSi) and Ag2Na have been computed to be -5210 and -29821.8 Jmol-1, respectively, with the desire to assist thermodynamic modeling. One set of self-consistent thermodynamic parameters is obtained for each of these binary systems. Comparisons between calculated and measured phase diagrams show that most of the experimental information can be satisfactorily accounted for by the present thermodynamic descriptions.